2020
DOI: 10.3390/rs12030352
|View full text |Cite
|
Sign up to set email alerts
|

Improved 3D Stem Mapping Method and Elliptic Hypothesis-Based DBH Estimation from Terrestrial Laser Scanning Data

Abstract: The detailed structure information under the forest canopy is important for forestry surveying. As a high-precision environmental sensing and measurement method, terrestrial laser scanning (TLS) is widely used in high-precision forestry surveying. In TLS-based forestry surveys, stem-mapping, which is focused on detecting and extracting trunks, is one of the core data processing tasks and the basis for the subsequent calculation of tree attributes; one of the most basic attributes is the diameter at breast heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…The experimental results showed that the leastsquares ellipse fitting method is more suitable for the estimation of DBH. Compared with other methods, the estimation accuracy of DBH of this method was improved, with the RMSE of 1.14 cm [30]. Wu et al [19] used a combination of ALS and TLS to manage fruit tree structure, number of trees, diseases, fertilization, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results showed that the leastsquares ellipse fitting method is more suitable for the estimation of DBH. Compared with other methods, the estimation accuracy of DBH of this method was improved, with the RMSE of 1.14 cm [30]. Wu et al [19] used a combination of ALS and TLS to manage fruit tree structure, number of trees, diseases, fertilization, etc.…”
Section: Discussionmentioning
confidence: 99%
“…We used the data collected by TLS to extract the DBH. In earlier studies, it was necessary to segment all the trees in the entire study area [30,47,48]. Due to the large amount of TLS points, low efficiency and high computational costs may occur when single tree segmentation is performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLS data have been used to estimate canopy characteristics outside of fire applications such as leaf area index [22], biomass [23,24], and canopy cover [25,26]. TLS collections have also targeted the mapping and measuring of individual trees [27,28]. More recently, TLS has been used to map fuels in three dimensions [29] and changes in forest structure following wildfire [30].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous tree localization methods for TLS point clouds can be categorized into two classes: model-fitting methods and feature-based methods. The model-fitting methods treat the tree localization as the detection of stems from point clouds [11][12][13]. Maas et al [14] divide tree point clouds into slices along the vertical direction and the circle fitting is applied to the sliced points, then model inliers of fitted circles will be recognized as stems.…”
Section: Introductionmentioning
confidence: 99%